2019
DOI: 10.3390/app9061155
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Modulus—Physical Parameters Relationship of Improved Red Clay by Dynamic Tri-Axial Test

Abstract: As one of the important parameters used in the analysis and design of subgrade, resilient modulus is directly related to the safety, economic and life time of subgrade structure. In this paper, the characteristics of resilient modulus of improved red clay at different additive content were studied through conducting laboratory repeated load tri-axial tests. The influence of stress state, moisture content, compactness, additive types, and content on resilient modulus were analyzed. In addition, the regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Also, the scale factor is 0.075, and there are 4483 zones and 6254 grid points in the model. Furthermore, this study adopts the constitutive model of the Mohr-Coulomb elastoplastic model, [22][23][24][25][26][27][28][29][30] that is, the Mohr-Coulomb yield criterion is used. The left and right boundaries are constrained in the horizontal direction, and the bottom boundary is fixed in all directions.…”
Section: Slope Model and Refined Safety Factor 21 Slope Modelmentioning
confidence: 99%
“…Also, the scale factor is 0.075, and there are 4483 zones and 6254 grid points in the model. Furthermore, this study adopts the constitutive model of the Mohr-Coulomb elastoplastic model, [22][23][24][25][26][27][28][29][30] that is, the Mohr-Coulomb yield criterion is used. The left and right boundaries are constrained in the horizontal direction, and the bottom boundary is fixed in all directions.…”
Section: Slope Model and Refined Safety Factor 21 Slope Modelmentioning
confidence: 99%
“…e red clay was widely distributed in southern China and it is often used as building materials or natural foundations of buildings. Since the red clay has swell-shrink characteristics and high plasticity index [1][2][3], it often induces many geo-hazards such as road cracking, uneven foundation settlement, slope instability, pit deformation, and destruction [4][5][6]. It was realized that the traditional soil solidifying materials such as cement, lime, and flyash had drawbacks of high costs and long construction periods, which could not meet the needs of the construction and social development [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thompson [23] described lime-reactive soils that show a significant increase in strength over time as reactive and those showing limited pozzolanic reactivity as non-reactive. Yuan et al [24] assessed the same lime and cement additions as improving agents of specific fine-grained soils-red clay. They found that the dynamic resilient modulus of red clay stabilised with cement is slightly higher in comparison to that with lime.…”
Section: Introductionmentioning
confidence: 99%